Etiologic Spectrum and Follow-Up Results of Noninfectious Uveitis in Children: A Single Referral Center Experience - Mustafa ÇAKAN,; Dilbade YILDIZ EKİNCİ,; Şerife GÜL KARADAG,; Nuray AKTAY AYAZ, (Archives of Rheumatology, 2019)
Objectives: This study aims to investigate the etiologic spectrum, demographic features, and long-term follow-up results of children with noninfectious uveitis (NIU). Patients and methods: Files of patients with NIU were reviewed between May 2010 and September 2017. The cohort consisted of 54 juvenile uveitis patients (26 males, 28 females; mean age 7.7 years; interquartile range [IQR] 9.2 years) with 93 affected eyes. Location of uveitis, laterality, age at onset of uveitis, complications of uveitis, duration of follow-up, associated systemic diseases, pertinent laboratory tests, medications used, and status of uveitis at the time of enrollment were recorded from the files. All patients had final systemic and ocular examination at the last month of enrollment. Results: Twenty-seven patients (50.0%) had juvenile idiopathic arthritis (JIA), 17 (31.4%) had idiopathic uveitis, six (11.1%) had Behçet disease (BD), and four (7.5%) had tubulointerstitial nephritis and uveitis (TINU) syndrome. Median duration of follow-up for uveitis was 16 (IQR: 15) months. Anterior uveitis was seen in 81.4% of the patients (65.9% had bilateral and 34.1% had unilateral anterior uveitis). Bilateral intermediate uveitis was observed in 11.2% and bilateral panuveitis in 7.4% of the patients. At the time of enrollment, 45 uveitis patients (83.3%) were under remission. Complications of uveitis were observed in 18.5% of the patients. Conclusion: Patients with JIA and BD should be regularly checked for uveitis. It is challenging to find an etiology in uveitis patients referred from ophthalmologists if initial questioning and examination do not reveal an overt rheumatologic disease. However, a simple urine test may help in establishing the diagnosis of TINU syndrome.